Object Relations, Buddhism, and Relationality in Womanist Practical Theology - Yetunde, Pamela Ayo (Black Religion/Womanist Thought/Social Justice, 2018)
This book establishes how Buddhism in the Insight Meditation tradition supports "remarkable relational resilience" for women who are of African descent and same-sex loving, yet living in a society that often invalidates women, African-Americans, LGBTQ people, and non-Christians. Pamela Ayo Yetunde explores the psycho-sexual experiences of African-American Buddhist lesbians, and shows that their abilities to be in healthy relationships are made possible through their Buddhist practices and communities, even in the face of invisibilizing forces related to racial, gender, sexuality, and religious discrimination and oppression.